Legal Reform and Loan Repayment: The Microeconomic Impact of Debt Recovery Tribunals in India - Sujata Visaria (2005)
This paper investigates the micro-level link between judicial quality and economic outcomes. It uses a loan-level data set from a large Indian bank to estimate the impact of a new quasi-legal institution, Debt Recovery Tribunals, aimed at accelerating banks' recovery of non-performing loans. I use a direrences-in-direrences strategy based on two sources of variation: the monetary threshold for claims to be eligible for these tribunals, and the staggered introduction of tribunals across Indian states. I _nd that the establishment of tribunals reduces delinquency in loan repayment by between 3 and 10 percent. The erect is significant within loans as well: for the same loan, installments that become due after the loan becomes treated are more likely to be paid up on time than those that become due before. Furthermore, interest rates on loans sanctioned after the reform are lower by 1-2 percentage points. These results suggest that legal reform and the improved enforcement of loan contracts can reduce borrower delinquency, and can lead banks to provide cheaper credit. Thus the paper illustrates a microeconomic mechanism through which improvements in legal institutions might stimulate economic growth